The Implementation of Safety Management: Construction Parties Perspective - Kee, Jasmine Sze Jye; Nik Fatma Arisya, Nik Yahya (2016)
This study intends to investigate on the implementation of an effective safety management and to enable the Malaysia construction industry to meet its Occupational Safety and Health obligations. This is due to the construction accidents which cause many human tragedies, de-motivate workers, delay project progress and adversely affect the overall cost of the project, productivity and reputation of the construction industry, safety aspects should be strictly emphasized especially within the construction site and the employees In meeting the objectives of the study, the research and data collection will be pointed out and the perspective of the construction parties, such as developers, quantity surveyors, architects, engineers and contractors in managing the safety. On top of that their opinions in terms of improving safety management have been gathered. Questionnaire surveys were distributed in the area of southern region (Johor) and central region (Selangor) of Peninsular Malaysia. From the surveys it revealed that the implementation of safety management is generally not satisfactory and construction parties still have rooms for improvement. Successful implementation needs modification of organizational culture and a safety management attitude. The management and employees must employ the participation or involvement approach to improve their workplace by focusing on psychosocial factors, health and safety risks in the workplace and reward and incentive schemes.